Temperature, stress and spontaneous mutation in Caenorhabditis briggsae and Caenorhabditis elegans - Matsuba, Chikako (The Royal Society, 2013)
Mutation rate often increases with environmental temperature, but establishing causality is complicated. Asymmetry between physiological stress and deviation from the optimal temperature means that temperature and stress are often confounded. We allowed mutations to accumulate in two species of Caenorhabditis for approximately 100 generations at 18°C and for approximately 165 generations at 26°C; 26°C is stressful for Caenorhabditis elegans but not for Caenorhabditis briggsae. We report mutation rates at a set of microsatellite loci and estimates of the per-generation decay of fitness (ΔM(w)), the genomic mutation rate for fitness (U) and the average effect of a new mutation (E[a]), assayed at both temperatures. In C. elegans, the microsatellite mutation rate is significantly greater at 26°C than at 18°C whereas in C. briggsae there is only a slight, non-significant increase in mutation rate at 26°C, consistent with stress-dependent mutation in C. elegans. The fitness data from both species qualitatively reinforce the microsatellite results. The fitness results of C. elegans are potentially complicated by selection but also suggest temperature-dependent mutation; the difference between the two species suggests that physiological stress plays a significant role in the mutational process.